ANALYSIS AND COMPLEX OF MEASURES, CARRIED OUT IN ESPTS-1, WITH THE AIM OF IMPROVEMENT OF THE MAIN TECHNICAL AND ECONOMIC INDICES OF THE BLAST STEEL FUMACE-2 WORKING - N. V. Andrianov; V. A. Matochkin; V. I. Djachenko; V. V. Pivtsajev; M. V. Ginejko (Литьë и металлургия)
Analysis and complex of measures, carried out in ESPTs-1 with the purpose of improvement of the main technical and economic indexes of blast steel furnace operation is given.